O. Hashimov's Artistic Interpretation of the Character of the Teacher in "Between Two Doors" - Soberova, Mohira (FILOLOGIYA UFQLARI JURNALI, 2024)
O. Hashimov's Artistic Interpretation of the Character of the Teacher in "Between Two Doors"